Testing and evaluation of physical strength of the sailors of laser radial - Ma, Y.; Zheng, W. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Physical strength is one of important factors that affect athletic performance. Based on scientific training, the research on testing and evaluating the physical strength for the sailors of the Laser Radial dinghy was carried out. Findings will provide guidance for accurate application and further perfection of scientific training.